Biomechanical considerations for tooth movement and strategies to avoid undesirable side effects - Jacob, Helder Baldi; Azeredo, Rafael Gonçalves; Spreafico, Carolina Servidoni [UNESP] (Elsevier, 2024)
Orthodontists prescribe forces to provide tooth movement, and performing it without understanding the fundamentals can put the treatment at risk. To get out of trouble in managing complex cases, orthodontists should understand biomechanics concepts and solutions, as well tooth movement biology. The correct application of the force system impacts the biological tissue responses inducing different responses in a favorable or unfavorable manner. The biomechanical domain prevents round tripping, unnecessary increase in treatment time, and damage to the dentoalveolar tissues. Indubitably, minimizing or preventing unnecessary tooth movement helps to decrease treatment time, which has been associated with root resorption and surrounding tissue damage. In the absence of the correct force system application (forces and moments), orthodontic treatment outcomes become unpredictable. Therefore, the key to success is the correct application of the biomechanics, and clinicians must have biomechanical knowledge and skill in reserve, which will be required when unfortunate surprises strike. If the knowledge is not available, orthodontists limit their success. So, in this article we present some information about the biology of orthodontic tooth movement and rationale biomechanics to prevent orthodontic tooth movement side effects, as well few cases and their biomechanics associated with the treatment.